HAK PENGUASAAN ATAS TANAH OLEH PEMILIK TANAH BERDASARKAN SURAT KETERANGAN RIWAYAT PEMILIK TANAH DI DESA TITI AKAR KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Irfan Hamdani; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Land Tenure Rights are rights protected by law and generally give authority to the right holder to physically control the land he owns. Land Certificate or SKT is a certificate made by the Head of the Village/Lurah based on the minutes of the land inspection and statements of community leaders, then corroborated by the Camat which contains information about the proof of land rights that have not been registered, in connection with the land will be transferred or will be the application for rights is filed.The problem discussed in this study is, Why do landowners who have a Land Ownership Certificate in Titi Akar Village, Rupat Utara District, Bengkalis Regency cannot control their land. How the efforts of landowners who have a Land Ownership Certificate in Titi Akar Village, Rupat Utara District, Bengkalis Regency can control their land.This type of research can be classified as sociological, because in this study the authors directly conducted research at the location under study in order to provide a complete picture of the problem under study. This research was conducted in Titi Akar Village, North Rupat District, Bengkalis Regency.From the results of the study it can be concluded two things. First, why landowners who have a Land Ownership Certificate or SKT cannot control their land are factors such as land legal knowledge, the lack of understanding of the SKT owners regarding the legal strength of a Land Certificate or SKT as proof of land ownership and there is no socialization about registration and land certification. Furthermore, rights are not processed and guarded and controlled by other parties. Second, the efforts of the owners of the Land Ownership Certificate or SKT in Titi Akar Village to control their land are the Efforts of the SKT Owner through the Titi Akar Village Head and Efforts through the Court or Litigation.Keywords: Tenure - Land - SKT